Association between Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers and Lung Cancer. Issue 9 (September 2021) - Helgeson, Scott A.; Waddle, Mark R.; Burnside, Rebecca C.; Debella, Yalew T.; Lee, Augustine S.; Burger, Charles D.; Li, Zhuo; Johnson, Patrick W.; Patel, Neal M.
Abstract : Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers were not associated with increased rates of lung cancer in a population-based study of >3 million patients. A beneficial effect in these medications was associated with earlier stage of diagnosis and decreased mortality. Supplemental digital content is available in the text. Abstract : Objectives: Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are the most commonly prescribed antihypertensives, with prior studies identifying a possible association between long-term use and increased rates of lung cancer. This study evaluated this potential association in a large population using propensity matching. Methods: This was a population-based cohort study in a large healthcare system in three regions of the United States. Pairwise propensity score matching was performed using demographics and comorbidities. All of the adult patients in the healthcare system from January 1, 2000 to April 30, 2018 with at least 1 year of follow-up were included. Results: In total, 3, 253, 811 patients with a median age of 59 (range 18–103) years were included. The ACEI group had a higher freedom from lung cancer versus controls at 15 years (98.47%, 95% confidence interval [CI] 98.41–98.54) versus 98.26%, (95% CI 98.20–98.33), whereas ARBs had similar rates versus controls at all time points. For patients diagnosed as having lung cancer, median all-cause survival was significantly higher in the ACEI (34.7 months, 95% CI 32.8–36.6) and ARB (30.9 months, 95% CI 28.1–33.8) groups than the control group (20.6 months, 95% CI 20.1–21.1). Conclusions: This study showed lower rates of lung cancer with ACEI use and no difference in risk with ARBs. In addition, use of these medications was found to be associated with increased survival in those diagnosed as having lung cancer. This study supports the continued use of these medications without concern for increasing the risk of lung cancer.